Novel bionic inspired nanosystem construction for precise delivery of mRNA - Yang, Taihua; Xia, Lei; Li, Gen; Zhao, Jie; Li, Jie; Ge, Jiahao; Yuan, Qinggong; Zhang, Jianjun; He, Kang; Xia, Qiang (Frontiers in Bioengineering and Biotechnology, 2023)
The intracellular delivery of messenger (m)RNA holds great potential for the discovery and development of vaccines and therapeutics. Yet, in many applications, a major obstacle to clinical translation of mRNA therapy is the lack of efficient strategy to precisely deliver RNA sequence to liver tissues and cells. In this study, we synthesized virus-like mesoporous silica (V-SiO2) nanoparticles for effectively deliver the therapeutic RNA. Then, the cationic polymer polyethylenimine (PEI) was included for the further silica surface modification (V-SiO2-P). Negatively charged mRNA motifs were successfully linked on the surface of V-SiO2 through electrostatic interactions with PEI (m@V-SiO2-P). Finally, the supported lipid bilayer (LB) was completely wrapped on the bionic inspired surface of the nanoparticles (m@V-SiO2-P/LB). Importantly, we found that, compared with traditional liposomes with mRNA loading (m@LNPs), the V-SiO2-P/LB bionic-like morphology effectively enhanced mRNA delivery effect to hepatocytes both in vitro and in vivo, and PEI modification concurrently promoted mRNA binding and intracellular lysosomal escape. Furthermore, m@V-SiO2-P increased the blood circulation time (t1/2 = 7 h) to be much longer than that of the m@LNPs (4.2 h). Understanding intracellular delivery mediated by the V-SiO2-P/LB nanosystem will inspire the next generation of highly efficient and effective mRNA therapies. In addition, the nanosystem can also be applied to the oral cavity, forehead, face and other orthotopic injections.